The roles of managers and acceptance of change in the public sector - Samah, Safuwan; Abu Samah, Bahaman; Suandi, Turiman; Idris, Khairuddin; Mohd Pauzi, Khairunnisa (Human Resource Management Academic Research Society, 2017)
Public sector plays a pivotal role in accelerating national development by progressively introducing and implementing series of change initiatives at all levels of public administration. In Malaysia, successful implementation of the change initiatives rest on the shoulder of the Administrative and Diplomatic Officers (ADO) whose managerial responsibilities cut across the most important administrative roles in the Malaysian Public Services (MPS). As their leadership roles continue to grow in significance, they constantly face various challenges in managing their subordinates towards achieving the common goals of the change initiatives. Thus, by having positive perceptions and attitudes towards change are crucial in promoting acceptance of change (AOC) behaviour among the ADO. However, negative perceptions and low attitude towards change would discourage the AOC, which would be detrimental to realizing the change initiatives in the public organizations. This study, therefore, aims to investigate the important roles of locus of control (LOC) and attitude towards change (ATC) in explaining the AOC behaviour among the middle managers in the MPS. A cross-sectional study was conducted by distributing self-administered questionnaires to a total of 400 respondents who were randomly sampled from the list of ADO. The findings revealed that the ATC indicated a statistically significant positive linear relationship with the AOC behaviour. However, the LOC was not statistically significant to explain the variance in AOC behaviour. This study provides new information for the Human Resource Development practitioner and can be used as input during change process in the context of public organisation. Several recommendations are briefly discussed to improve the AOC behaviour towards the end of this paper.